Dark top partner - Haiying Cai; Giacomo Cacciapaglia (Journal of High Energy Physics, 2023)
Abstract Composite Higgs models with extended symmetries can feature mesonic dark matter candidates. In fundamental CHMs, the origin of dark parity can be explained in the UV theory. Combined with top partial compositeness, this leads to non-chiral Yukawa interaction connecting mesonic DM with one dark top partner and one SM top. We examine the DM phenomenology in SU(6)/SO(6) and SU(6)/Sp(6) CHMs with the presence of dark top partners. Phenomenological constraints require the mass of top partner in even parity to be of the multi-TeV order.